THE ECONOMIC AND ECOLOGICAL SIGNIFICANCE OF NITROGEN AND PHOSPHORUS COMPOUNDS IN NATIONAL ECONOMY - Botirova Sabogul Rahmatullayevna; O‘rinova Durdona Sherzod qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Nitrogen and phosphorus compounds play a crucial role in various sectors of the national economy, including agriculture, industry, and environmental management. These compounds are essential for increasing crop yields, improving soil fertility, and supporting industrial processes. However, their excessive or uncontrolled use can lead to environmental problems such as water pollution, eutrophication, and soil degradation. This article analyzes both the economic benefits and ecological challenges associated with the use of nitrogen and phosphorus compounds, emphasizing the need for sustainable management practices.